How economic factors influence fertility rates - Saturka, Lukáš (2025)
This thesis analyses the macroeconomic and social determinants of fertility in the European Union using panel data from 2000 to 2023. It applies fixed-effects regression models to test how economic development, unemployment, inflation, education, and public spending affect fertility rates across 27 member states. The analysis shows that fertility is influenced by both economic and social factors. Countries’ economic development has a significant influence on fertility decisions, but fertility declines once a certain threshold is reached. Inflation and female unemployment usually reduce fertility, while the level of female education, the marriage rate, and the average age at first birth have more complex, non-linear effects. This thesis demonstrates that while economic conditions are the most powerful predictors of fertility trends, cultural and social factors also play a crucial role. When considered together, they offer a much clearer explanation of fertility behaviour than either dimension alone. The findings suggest that policies addressing fertility should not focus only on economic growth or financial incentives but also consider social and cultural structures.